Pathogens Associated with Sugarcane Borers, Diatraea spp. (Lepidoptera: Crambidae): A Review - Hernández-Velázquez, Víctor M.; Lina-García, Laura P.; Obregón-Barboza, Verónica; Trejo-Loyo, Adriana G.; Peña-Chora, Guadalupe (International Journal of Zoology, 2012)
The objective of this paper was to analyze information related to entomopathogenic-associated Diatraea spp. Gaining a better understanding of the effects of these microorganisms will help in the development of successful microbial control strategies against stem borers that attack sugarcane plants.